Pengaruh Massa Sodium Dodecyl Sulfate terhadap Nilai Bandgap Semikonduktor TiO₂-ZnO - Valen Febri Adha; Sherly Kasuma Warda Ningsih; Hardeli Hardeli (MASALIQ, 2025)
Modification of the TiO₂-ZnO semiconductor through the addition of Sodium Dodecyl Sulfate (SDS) has been carried out to reduce the bandgap energy using the sol-gel method. The SDS mass variations used in the synthesis process were 0.015, 0.020, 0.025, 0.030, and 0.035 grams. The synthesized samples were characterized using UV-Vis Diffuse Reflectance Spectroscopy (DRS) to determine the bandgap values. The characterization results showed that the addition of 0.025 grams of SDS produced the lowest bandgap value, measured at 3.16 eV. This reduction in bandgap is attributed to changes in the material's physical and chemical surface structure, influenced by the interaction between the surfactant and the TiO₂-ZnO surface, microstructural alterations, and modifications in crystallinity. However, at higher SDS concentrations (≥0.025 grams), the bandgap value increased again, due to particle agglomeration and hindered electron transfer. These findings indicate that the addition of SDS surfactant within an optimal range can enhance the optical properties of semiconductor materials, while excessive addition may degrade performance due to undesirable morphological changes.